Analisis Perbandingan Rencana Anggaran Biaya (RAB) Dengan Standar Kementrian PUPR Tahun 2022 Dan SNI Tahun 2008 Pada Proyek Pembangunan Gedung: (Studi Kasus: Pembangunan Gedung Badan Pengelola Pajak Dan Retribusi Daerah Di Papua Barat Daya) - Hesa W, Muhammad; Syara, Elfiyusriningsi; Rizal S, Muh (CV. Shofanah Media Berkah, 2024)
The construction project of the Regional Tax and Levy Management Agency Office Building is located in Mariat Pantai, Aimas District, Sorong Regency, Southwest Papua. The project is an effort by the local government to improve the quality of infrastructure in the coastal Mariyat area where the office building was built to meet safety and health standards. The method in this study is quantitative research. Quantitative research is a research method that collects and analyzes data based on numbers and numerical measurements. The analysis shows that by using the SNI analysis, the results are Rp. 729,477,142,- while by using PUPR, the results are Rp. 809,271,989,- which means that the SNI analysis is more economical than the PUPR analysis. The final results of the study show that the calculation of the cost of building the office building of the Regional Tax and Levy Management Agency using the 2008 SNI analysis is Rp. 729,477.42 while the result of the cost estimate using the 2022 PUPR analysis is Rp. 809,271,989. From the calculation results, the comparison of the cost budget estimate between the 2008 SNI and PUPR 2023 methods, namely the 2022 PUPR method is Rp. 79,794,847 more expensive than the 2008 SNI.